2008
DOI: 10.1177/0003319707309651
|View full text |Cite
|
Sign up to set email alerts
|

In-Stent Stenosis: Potential Role of Increased Oxidative Stress and Glutathione-Linked Detoxification Mechanisms

Abstract: This study was designed to determine whether red-cell oxidative stress status and antioxidant enzyme levels can serve as markers in patients predisposed to in-stent stenosis. Blood was collected from patient groups undergoing coronary angiography for chest pain evaluation, namely, group A (without coronary artery disease), group B (previous coronary stents without in-stent stenosis), and group C (previous coronary stents with in-stent stenosis). Thiobarbituric acid reactive substances (measure of lipid peroxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 25 publications
3
13
0
Order By: Relevance
“…In previous studies, significant results were obtained concerning GPx, but the participating groups were usually chosen among sportsmen, healthy people or CAD patients but not from an intermediate group (23,24). In concordance with our study, the association between CAD and the increase or decrease of basal GPx levels is examined (10)(11)25). In a previous study evaluating syndrome X and SOD activity it is shown that the increased SOD activity would reduce complaints and increase the quality of life in patients with syndrome X (22,26).…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…In previous studies, significant results were obtained concerning GPx, but the participating groups were usually chosen among sportsmen, healthy people or CAD patients but not from an intermediate group (23,24). In concordance with our study, the association between CAD and the increase or decrease of basal GPx levels is examined (10)(11)25). In a previous study evaluating syndrome X and SOD activity it is shown that the increased SOD activity would reduce complaints and increase the quality of life in patients with syndrome X (22,26).…”
Section: Discussionsupporting
confidence: 80%
“…It has been thought that, slow coronary flow and syndrome X are part of this process (2)(3)(4)(5)(6)(7)(8)(9). The relation between oxidant enzyme level and coronary artery disease has been revealed by previous studies (10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 94%
“…In combination with this magnetic guidance strategy, antioxidant enzyme-loaded MNP whose efficacy has been demonstrated in the present study may be an interesting candidate for a stent-targeted antirestenotic therapy. A rationale for exploring the potential of antioxidant enzymes, SOD and catalase, either alone or in combination, for preventing restenosis is based on the major contribution of ROS to the cascade of events eventually resulting in the vessel reobstruction [36, 37], with a proof-of-concept provided in previous studies using gene vectors encoding these proteins [38, 39]. …”
Section: Discussionmentioning
confidence: 99%
“…ISR and metal ions are both known to stimulate increased oxidative stress and a reduction in anti-oxidant enzymes [37]. VSMCs treated with SS ions were measured for the generation of hydrogen peroxide (H 2 O 2 ).…”
Section: Resultsmentioning
confidence: 99%